Efficacy of mass drug administration with ivermectin for control of scabies and impetigo, with coadministration of azithromycin: a single-arm community intervention trial. Issue 5 (May 2019) - Romani, Lucia; Marks, Michael; Sokana, Oliver; Nasi, Titus; Kamoriki, Bakaai; Cordell, Billie; Wand, Handan; Whitfeld, Margot J; Engelman, Daniel; Solomon, Anthony W; Kaldor, John M; Steer, Andrew C
Summary: Background: In small community-based trials, mass drug administration of ivermectin has been shown to substantially decrease the prevalence of both scabies and secondary impetigo; however, their effect at large scale is untested. Additionally, combined mass administration of drugs for two or more neglected diseases has potential practical advantages, but efficacy of potential combinations should be confirmed. Methods: The azithromycin ivermectin mass drug administration (AIM) trial was a prospective, single-arm, before-and-after, community intervention study to assess the efficacy of mass drug administration of ivermectin for scabies and impetigo, with coadministration of azithromycin for trachoma. Mass drug administration was offered to the entire population of Choiseul Province, Solomon Islands, and of this population we randomly selected two sets of ten sentinel villages for monitoring, one at baseline and the other at 12 months. Participants were offered a single dose of 20 mg/kg azithromycin, using weight-based bands. Children weighing less than 12·5 kg received azithromycin oral suspension (20 mg/kg), and infants younger than 6 months received topical 1% tetracycline ointment. For ivermectin, participants were offered two doses of oral ivermectin 200 μg/kg 7–14 days apart using weight-based bands, or 5% permethrin cream 7–14 days apart if ivermectin was contraindicated. Our study had the primary outcomes of safety and feasibility of large-scale mass coadministration of oral ivermectin and azithromycin, which have been previously reported. We report here the prevalence of scabies and impetigo in residents of the ten baseline villages compared with those in the ten 12-month villages, as measured by examination of the skin, which was a secondary outcome of the trial. Further outcomes were comparison of the number of all-cause outpatient attendances at government clinics in Choiseul Province at various timepoints before and after mass drug administration. The trial was registered with the Australian and New Zealand Trials Registry (ACTRN12615001199505). Findings: During September, 2015, over 4 weeks, 26 188 people (99·3% of the estimated population of Choiseul [n=26 372] as determined at the 2009 census) were treated. At baseline, 1399 (84·2%) of 1662 people living in the first ten villages had their skin examined, of whom 261 (18·7%) had scabies and 347 (24·8%) had impetigo. At 12 months after mass drug administration, 1261 (77·6%) of 1625 people in the second set of ten villages had their skin examined, of whom 29 (2·3%) had scabies (relative reduction 88%, 95% CI 76·5–99·3) and 81 (6·4%) had impetigo (relative reduction 74%, 63·4–84·7). In the 3 months after mass drug administration, 10 614 attended outpatient clinics for any reason compared with 16 602 in the 3 months before administration (decrease of 36·1%, 95% CI 34·7–37·6), and during this period attendance for skin sores, boils, and abscesses decreased by 50·9% (95% CI 48·6–53·1). Interpretation: Ivermectin-based mass drug administration can be scaled to a population of over 25 000 with high efficacy and this level of efficacy can be achieved when mass drug administration for scabies is integrated with mass drug administration of azithromycin for trachoma. These findings will contribute to development of population-level control strategies. Further research is needed to assess durability and scalability of mass drug administration in larger, non-island populations, and to assess its effect on the severe bacterial complications of scabies. Funding: International Trachoma Initiative, Murdoch Children's Research Institute, Scobie and Claire Mackinnon Trust, and the Wellcome Trust.